Redescription of Schistura myrmekia (Fowler 1935) (Teleostei: Nemacheilidae) - Singer, Randal A.; Page, Lawrence M. (Zootaxa, 2012)
Schistura myrmekia (Fowler 1935) was originally described from a single specimen collected from Keng Sok,southwestern Thailand. It was differentiated from a similar species, S. desmotes (Fowler 1934), by having four—ratherthan three—dark bands behind the dorsal fin, and the presence of a wart-like suborbital flap. Although S. myrmekia hassince been placed in the synonymy of S. desmotes, it is distinguishable by the size and orientation of the suborbital flap,a much shorter maxillary barbel, and a more slender appearance. The holotype, the only known specimen of S. myrmekia,is redescribed and contrasted with other species of Schistura in southern Thailand. Schistura myrmekia is known onlyfrom the holotype, collected in an area that recently has been highly modified by human activities. Recent efforts to find the species have failed, and it is probably extinct.